Characterization of the Tomato (Solanum lycopersicum) Pectin Methylesterases: Evolution, Activity of Isoforms and Expression During Fruit Ripening - Wen, Bo; Zhang, Feng; Wu, Xiaozhen; Li, Huan (Frontiers in Plant Science, 2020)
Pectin methylesterase (PME, EC 3.1.1.11) is a hydrolytic enzyme of pectin that plays multiple roles in different plant development processes and responses to biotic stress. To characterize the molecular evolution and functional divergence of the PME gene family, a genome-wide analysis of the PME gene family in the tomato was performed. In total, 57 nonredundant PME genes were identified, and these PME genes were divided into five groups based on their phylogeneny; their classification was supported by similar gene structures and domain distributions. The PME genes were found to be unevenly distributed among 12 chromosomes of the tomato. In addition, 11 segmental duplication and 11 tandem duplication events occurred in these PME genes, implying that both contributed to the expansion of the tomato PME gene family. Nonsynonymous/synonymous mutation ratio analysis revealed that positive selection played a key role in the functional divergence of PME genes. Interspecific collinear analysis indicated a large divergence in the PME gene family after the divergence of monocot and dicot plants in ancient times. Gene expression pattern analysis suggested that PMEs plays roles in the different parts of the tomato plant, including the fruit. Three newly identified candidate genes (Solyc03g083360, Solyc07g071600, and Solyc12g098340) may have functions during fruit ripening. Immunoassays suggested that the tomato isoform PE1 and PE2 may change pectin structure at cell junctions, which could be associated with fruit softening. In addition, our analysis indicate that two undescribed PE isoforms might be active in leaves and fruits. This study increases our understanding of the PME gene family in the tomato and may facilitate further functional analyses to elucidate PME function, especially during fruit ripening.